MENINGKATKAN MUTU PENDIDIKAN MELALUI MANAJEMEN SEKOLAH DI SDN 2 DUWET KABUPATEN SITUBONDO - Mory Victor Febrianto (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2018)
Management or management are integral components and cannot be implemented from the overall education process. The reason is that without management it is impossible for education goals to be realized optimally, effectively and efficiently. The concept applies in schools that demand effective and efficient management. For this reason, it is necessary to understand the main functions of management, namely planning, implementation, supervision and coaching. The purpose of this study was to determine school management in improving the quality of education, including: (1) Planning school programs; (2) Implementation of school programs and (3) obstacles faced. This study uses a qualitative approach with descriptive methods, data collection techniques are carried out through interview guidelines, observation guidelines, and documentation studies. Research subjects were school principals, supervisors and teachers at SD Negeri 2 Duwet, Situbondo Regency. The results of his research were found: (1) Planning school programs include: teaching programs, including: the need for teachers to distribute teaching assignments, procurement of textbooks, learning tools and teaching aids, procurement or development of school laboratories, procurement or development of school libraries, assessment system of learning outcomes, and curricular activities; (2) The implementation of the school program, namely the strategy applied to achieve an improvement in the quality of education, including: program socialization, SWOT analysis, problem solving, quality improvement, and monitoring and evaluation of the implementation of school programs; and (3) Barriers to school program planning, including lack of community participation and economic difficulties so that their support for school management is low. It is expected that supervisors can direct and supervise the school principal in improving the quality of education about school program planning, program implementation and the obstacles it faces in an effective, effective and efficient manner so that the quality of education in the school can be improved